Prognosis and Prognostic Factors of Serous Borderline Tumor-Micropapillary Variant: Retrospective Study of 200 Patients with Long-Term Follow-Up. (10th October 2022) - Jia, Shuang-Zheng; Yao, Hong-Wen; Li, Ning; Yang, Jun-Jun; Xiang, Yang; Zheng, Shan; Leng, Jin-Hua; Wu, Ling-Ying
Abstract : Objective . To determine the oncofertility outcomes and prognostic factors in a large series of serous borderline ovarian tumor-micropapillary variant (SBOT-M) with a long-term follow-up. Methods . Consecutive patients with SBOT-Ms treated from two affiliated hospitals of the Chinese Academy of Medical Sciences were retrospectively reviewed. Prognostic factors on invasive recurrence, disease-free survival (DFS), and overall survival were analyzed, and outcomes of patients treated with conservative and radical surgery were compared. Results . From 2000 to 2020, 200 patients were identified and followed. After a median follow-up of 68 months, 81 patients relapsed. In the multivariate analyses, younger age at diagnosis and conservative surgery that preserved fertility potential were independently associated with worse DFS (p = 0.018 and <0.001, respectively). Twenty-three patients experienced invasive recurrence, and seven died of progressive disease. Multivariate analysis showed that nulliparous and advanced FIGO stage were independently adversely associated with lethal recurrence (p = 0.022 and 0.029, respectively). Only advanced FIGO stage at diagnosis was associated with worse overall survival at univariate analysis (p = 0.02 ). Among 61 patients attempting conception, 37 achieved 44 pregnancies and resulted in 32 live births. Conclusions . In this series, patients with SBOT-M have an acceptable oncofertility outcomes. The use of conservative surgery was independently associated with worse DFS, but without an impact on neither invasive relapse nor on overall survival. Patients with advanced FIGO stages had a significantly higher risk of lethal recurrence and worse overall survival, suggesting that adequate staging surgery and intensive postoperative surveillance should be warranted.